Say Nothing: A True Story of Murder and Memory in Northern Ireland - Keefe, Patrick Radden 1976- (New York Doubleday, 2019)
"A narrative about a notorious killing that took place in Northern Ireland during The Troubles and its devastating repercussions to this day"--
Includes bibliographical references (pages 423-427) and index.
Keywords: McConville, Jean; Irish Republican Army; TRUE CRIME / Murder / General; HISTORY / Europe / Ireland; Abduction -- History -- Northern Ireland; Murder -- History -- Northern Ireland; True crime stories